1997
DOI: 10.1121/1.419376
|View full text |Cite
|
Sign up to set email alerts
|

Detection of silent intervals between noises activating different perceptual channels: Some properties of “central” auditory gap detection

Abstract: This article describes four experiments on gap detection by normal listeners, with the general goal being to examine the consequences of using noises in different perceptual channels to delimit a silent temporal gap to be detected. In experiment 1, subjects were presented with pairs of narrow-band noise sequences. The leading element in each pair had a center frequency of 2 kHz and the trailing element's center frequency was parametrically varied. Gap detection thresholds became increasingly poor, sometimes by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
227
5
29

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(287 citation statements)
references
References 42 publications
26
227
5
29
Order By: Relevance
“…Acoustic onsets are known to have a privileged status with respect both to perception and to auditory cortical discharge (Phillips & Heining, 2002). They are especially important in speech perception for phonetic identification (Phillips, Taylor, Hall, Carr, & Mossop, 1997) and even in music perception for identification of timbre and the type of instrument producing sound (Saldanha & Corso, 1964). Timbre is a biologically significant feature of natural sounds.…”
Section: Learning Strategies and Cortical Plasticitymentioning
confidence: 99%
“…Acoustic onsets are known to have a privileged status with respect both to perception and to auditory cortical discharge (Phillips & Heining, 2002). They are especially important in speech perception for phonetic identification (Phillips, Taylor, Hall, Carr, & Mossop, 1997) and even in music perception for identification of timbre and the type of instrument producing sound (Saldanha & Corso, 1964). Timbre is a biologically significant feature of natural sounds.…”
Section: Learning Strategies and Cortical Plasticitymentioning
confidence: 99%
“…GDTs were obtained monotically from the right ear using stimuli and methods identical to those used previously in our laboratory (e.g., Lister & Roberts, 2005;Lister, et al, 2002) and similar to those used by others (e.g., Phillips, et al, 1997). There were two stages in obtaining behavioral GDTs.…”
Section: Psychophysical Gap Detectionmentioning
confidence: 99%
“…When the noise bands that mark the gap are of different frequencies, known as across-channel gap detection, the task is more difficult and GDTs are larger (Lister & Roberts, 2005;Lister, et al, 2002). Because the phonemes that precede and follow temporal cues in speech are never identical, across-channel gap detection is thought to be more representative of the temporal cues important for speech perception than within-channel gap detection (Formby, Gerber, Sherlock, & Magder, 1998;Phillips, Taylor, Hall, Carr, & Mossop, 1997); therefore, this condition has received great interest in recent years.It has been suggested that detection of gaps between markers that are close (or overlap) in frequency is relatively easy because it requires monitoring activity in a single neural channel. For gaps between markers that differ in frequency, the listener must make a decision regarding the relative timing between the offset of neural activity in one channel and the onset in an entirely different channel (Formby, et al, 1998;Grose, Hall, Buss, & Hatch, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] The auditory ability for temporal resolution is the minimum time required for separating or resolving acoustic events. 8,9 In trying to locate the physiological mechanism of temporal resolution, some authors have suggested that auditory nerve fibers participate significantly in the process.…”
Section: Introductionmentioning
confidence: 99%